Kinerja Pegawai Ditinjau Dari Kompetensi, Kompensasi, Motivasi Kerja, dan Disiplin Kerja - Yenni Rosyinah Hasibuan; Fitria Ridha Ningsih; Yuliarni Putri (Fakultas Ekonomi Universitas Andalas, 2023)
The success of the hospital in providing the best and quality service to the community can be measured by the quality of the performance of its human resources. This is because human resources are an important element involved in the core activities of providing health services in a hospital. This study aims to analyze several factors that have an influence on employee performance at RSUD Dr. Rasidin Padang, namely commitment, compensation, work motivation, and work discipline. The analytical method used in this research is path analysis using the help of the SPSS for windows program. This study used 158 respondents as the research sample. The independent variables consist of Competence (X1), Compensation (X2), Work Motivation (X3), and Work Discipline (X4), while the dependent variable is Performance (Y). The results showed that competence, compensation, work motivation, and work discipline had a significant positive effect on the performance of RSDU Dr. Rasidin Padang. Keyowords : Competence, Compensation, Work Motivation, Work Dicipline, and Employee Performance